Respuesta :

Answer:

ne solution was found :

                  r = -2

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :  

               8*(x+6)-10+r-(3*(x+12)+5*x)=0  

Step by step solution :

Step  1  :

Equation at the end of step  1  :

 (((8•(x+6))-10)+r)-(3•(x+12)+5x)  = 0  

Step  2  :

Equation at the end of step  2  :

 ((8 • (x + 6) -  10) +  r) -  (8x + 36)  = 0  

Step  3  :

Equation at the end of step  3  :

 r + 2  = 0  

Step  4  :

Solving a Single Variable Equation :

4.1      Solve  :    r+2 = 0  

Subtract  2  from both sides of the equation :  

                     r = -2  

One solution was found :

                  r = -2


Step-by-step explanation: